TV and Minors: the Reasons for Violence - Iannaccone, Antonio (Italian Sociological Review, 2015)
Thousands of different questions are centered on the topic of TV violence, especially those concerning young spectators. In everyday life, children, youth and adolescents watch particularly brutal and heightened scenes on TV, which, however, it is not always legitimate to condemn. In fact, if we assume that apocalyptic positions (together with integrated stances) bring nowhere, perhaps it will be possible to give life to a minors friendly television, taking advantage of the numerous existing family mediation and self-regulation strategies. The code teaches it.